Assessing the Effectiveness of the Ghana Maritime Authority in Managing the Maritime Industry in Ghana - Cobbah, Stella (2013)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters of Business Administration, June, 2012